Mercury Methylation by Cobalt Corrinoids: Relativistic Effects Dictate the Reaction Mechanism. Issue 38 (11th August 2016) - Demissie, Taye B.; Garabato, Brady D.; Ruud, Kenneth; Kozlowski, Pawel M.
Abstract: The methylation of Hg II (SCH3 )2 by corrinoid‐based methyl donors proceeds in a concerted manner through a single transition state by transfer of a methyl radical, in contrast to previously proposed reaction mechanisms. This reaction mechanism is a consequence of relativistic effects that lower the energies of the mercury 6p1/2 and 6p3/2 orbitals, making them energetically accessible for chemical bonding. In the absence of spin–orbit coupling, the predicted reaction mechanism is qualitatively different. This is the first example of relativity being decisive for the nature of an observed enzymatic reaction mechanism. Abstract : Of relative importance : The methylation of Hg II (SCH3 )2 by corrinoid‐based methyl donors proceeds in a concerted manner through a single transition state by transfer of a methyl radical. This reaction mechanism is a consequence of relativistic effects, and constitutes the first example of relativity being decisive for the nature of an enzymatic reaction mechanism. SOC=spin–orbit coupling.